Developing an Interactive Multimedia Based on Local Culture for Teaching Writing Narrative Texts for the Eighth Graders - sulistiyanto, sigit; Faridi, Abdurrachman; Saleh, Mursid (Universitas Negeri Semarang, 2018)
This study describes developing an interactive multimedia based on local culture for teaching writing narrative texts for the eighth graders. In the process of developing the materials, this study addressed four problems: (1) What are existing materials available to teach students of eight graders of Junior High School?(2) What is the initial condition of students before using the narrative texts materials developed based on local culture through interactive multimedia?(3) How is interactive multimedia developed based on local culture for year eight students of junior high school?(4) How effective is the developed interactive multimedia based on local culture used for teaching writing narrative text?.In developing the narrative text materials through interactive multimedia, the method, Research and Development (R & D) was adapted and simplified from the development stages of Borg and Gall. The process started from doing a survey. Then, it was followed by developing materials through interactive multimedia, experts and teachers validation, doing first revision, trying out the materials, doing second revision, and ended by producing the final product. The developed product is the materials of narrative text through interactive multimedia. The result of the narrative text learning media was narrative corner, grammar pitstop, writing section, and evaluation.